Turkish migrants adjust body height during adolescence to the host community in Germany - Jana Fritsch; Christiane Scheffler (Human Biology and Public Health)
Background Investigating migration is crucial for understanding population changes and their impact on growth. Migration and its associated Social-Economic-Political-Emotional (SEPE) factors can influence height, aligning with the theory of “developmental plasticity”, which suggests that environmental stimuli affect growth patterns.